Pengaruh Environmental Regulation terhadap Environmental Performance Melalui Mediasi Corporate Social Responsibility - Zaim, Ryanda Luthfi; Lukman, Syukri; Syafrizal (Jurnal Informatika Ekonomi Bisnis, 2023)
Efforts to realize a sustainable palm oil industry from upstream to downstream encourage companies to implement environmental regulations and corporate social responsibility that are carried out by multiple parties in the palm oil industry sector. This study aims to prove the effect of environmental regulation and corporate social responsibility on environmental performance, as well as to provide a mediating effect of corporate social responsibility on the relationship between environmental regulation and environmental performance. Data collection is done through the sustainability report of each company. Based on the results of testing the hypothesis found that environmental regulations have a positive but not significant effect on environmental performance, environmental regulations have a positive and significant effect on corporate social responsibility, corporate social responsibility has a positive and significant effect on environmental performance, and corporate social responsibility mediates the relationship between environmental regulations with environmental performance in oil palm plantation companies in Indonesia.